2015
DOI: 10.1186/s13071-015-1028-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IFN-γ and TGF-β in the functional activity of mononuclear cells in the presence of Entamoeba histolytica

Abstract: BackgroundEntamoeba histolytica (E. histolytica) causes amoebiasis, which is a disease with significant morbidity and mortality. Phagocytic cells and cytokines appear to be important in amoebiasis, but very little is known about the influence of these cells and cytokines in protozoan infections. The aim of this study was to analyse the supernatant of cultures of mononuclear (MN) cells with E. histolytica to determine: 1) the levels of the cytokines IFN-γ and TGF-β, and 2) the amoebicidal activity of MN cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In addition, Meza et al ( 2014 ) demonstrated that virgin T-cell differentiation into Th17 cells producing IL-17 occurred after the direct stimulation with other cytokines such as TGFβ, IL-6, and IL-1 in a murine model of infection with Trypanosoma cruzi . Moraes et al ( 2015 ) reported that mononuclear cells collected from healthy individuals incubated with E. histolytica in culture induced the production of IFN γ and TGFβ, and that both had a beneficial effect on the modulation of the activity of these cells. Our results agree with data of Moraes regarding the effects on IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Meza et al ( 2014 ) demonstrated that virgin T-cell differentiation into Th17 cells producing IL-17 occurred after the direct stimulation with other cytokines such as TGFβ, IL-6, and IL-1 in a murine model of infection with Trypanosoma cruzi . Moraes et al ( 2015 ) reported that mononuclear cells collected from healthy individuals incubated with E. histolytica in culture induced the production of IFN γ and TGFβ, and that both had a beneficial effect on the modulation of the activity of these cells. Our results agree with data of Moraes regarding the effects on IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, leucocytes activated by TGF-b and IFN-c diminish E. histolytica viability by 10%. (15). On the other hand, in vitro studies demonstrated that contact with myeloperoxidase and hydrogen peroxide reduced E. histolytica viability by 90% (16).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines, the levels of which correlate with the degree of tissue damage, are released by attacked host cells or effector cells. IFN-γ is a suppressive cytokine that can clear the parasite [ 45 ]. In the present study, there was no significant increase in IFN-γ during ALA development in hamsters, perhaps suggesting that persistent progression of lesions facilitates invasive amebiasis.…”
Section: Discussionmentioning
confidence: 99%